Immune Pathways in Etiology, Acute Phase, and Chronic Sequelae of Ischemic Stroke. Issue 8 (15th April 2022) - Endres, Matthias; Moro, Maria A.; Nolte, Christian H.; Dames, Claudia; Buckwalter, Marion S.; Meisel, Andreas
Abstract : Inflammation and immune mechanisms are crucially involved in the pathophysiology of the development, acute damage cascades, and chronic course after ischemic stroke. Atherosclerosis is an inflammatory disease, and, in addition to classical risk factors, maladaptive immune mechanisms lead to an increased risk of stroke. Accordingly, individuals with signs of inflammation or corresponding biomarkers have an increased risk of stroke. Anti-inflammatory drugs, such as IL (interleukin)-1β blockers, methotrexate, or colchicine, represent attractive treatment strategies to prevent vascular events and stroke. Lately, the COVID-19 pandemic shows a clear association between SARS-CoV2 infections and increased risk of cerebrovascular events. Furthermore, mechanisms of both innate and adaptive immune systems influence cerebral damage cascades after ischemic stroke. Neutrophils, monocytes, and microglia, as well as T and B lymphocytes each play complex interdependent roles that synergize to remove dead tissue but also can cause bystander injury to intact brain cells and generate maladaptive chronic inflammation. Chronic systemic inflammation and comorbid infections may unfavorably influence both outcome after stroke and recurrence risk for further stroke. In addition, stroke triggers specific immune depression, which in turn can promote infections. Recent research is now increasingly addressing the question of the extent to which immune mechanisms may influence long-term outcome after stroke and, in particular, cause specific complications such as poststroke dementia or even poststroke depression.